Introduction to SAVI's way of working - State Accountability and Voice Initiative (SAVI) - SAVI (DFID, 2015)
We are piloting a new approach to identifying and supporting our partn ers.  This breaks with convention in many ways in order to improve imp act.  SAVI Approach Papers summarise key aspects of SAVI’s way of work ing. They explain what we do, and why – and link to relevant tools and frameworks. Our approach is summarized in...
Keywords: Practice